The influence of anti-federal factions in Sabah politics: an assessment - Jeniwaty Mohd Jody; Mohammad Agus Yusoff; Jamaie Hamil (Penerbit Universiti Kebangsaan Malaysia, 2024)
The discontent among the populace of Sabah towards the federal government has contributed to the emergence and growth of anti-federal factions within the state. It has been argued that the federal government has engaged in discriminatory practices towards Sabah, resulting in a significant lag in development compared to other states. As a result, these organisations appealed to the public, urging Sabah to secede from the Federation of Malaysia. This article investigates the reasons that led to the formation of anti-federal organisations in Sabah. The primary source used in this article, employing the anti-federal notion as an analytical tool, consists of an interview, while the secondary sources encompass books, journal articles and newspaper publications. This article contends that four major elements fuelled the creation of anti-federal factions in Sabah: historical considerations; ethnic distinctions; language, culture, and religion; as well as economic issues due to federal government control. All of these issues led to the formation of anti-federal organisations in Sabah, including the Sabah-Sarawak Keluar Malaysia (SSKM), Borneo’s Plight in Malaysia Foundation (BOPIM), United Borneo Front (UBF), and Momogun Seek For Self-Determination (MOSIK). All anti-federal organisations have worked to promote the anti-federal movement in Sabah to encourage the state to secede from the Malaysian Federation, but their efforts remained futile. This phenomenon might be attributed to the perception that their influence is limited inside the interior region and that the majority of anti-federal factions in Sabah exhibited a preference for functioning as non-governmental entities rather than engaging in political activities.